Peningkatan Kualitas Hidup melalui Deteksi Dini Penyakit Degeneratif melalui Pemeriksaan Tekanan Darah dan Glukosa Darah - Faiza, Eva Inayatul; Akbarani, Riski; Mauludiyah, Indah (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Background: Degenerative diseases are still a health problem that must be paid attention to. This disease can be prevented by early detection so as to minimize the risk factors that cause it. Various government efforts have been made to prevent and treat degenerative diseases, one of which is early detection of disease through regular blood pressure checks and blood sugar checks. Activity objective: community service is to improve the quality of life through early detection of degenerative diseases through blood pressure and blood glucose checks. Method: Community service method using free blood pressure and blood glucose checks and providing counseling about degenerative diseases. Community service recommendations for 37 people carried out on August 23 2024. Results: Most blood pressure and blood glucose examination results were within normal limits. Conclusion: Community service activities were carried out smoothly and we hope that this activity can pay attention to the quality of life, especially related to degenerative diseases. Keywords: Early Detection: Degenerative Disease